An oil-water hydrogel dressing, a forming mold and a preparation method

CN122894547APending Publication Date: 2026-10-13NORTHWEST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611388132.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]然而,聚氨酯泡沫敷料内部多孔结构在面对高粘度液体时,其毛细管吸收或转运能力不足以驱动液体快速渗透和扩散,极易发生孔道堵塞,导致液体在敷料-创面界面大量滞留

Benefits of technology

1、本发明的油水凝胶敷料利用锥形微通道内壁的润湿性梯度,且沿油水凝胶复合基质体的厚度方向具有连续变化的相分布,通过锥形微通道的几何形状与锥形微通道内壁的连续润湿性梯度”的深度耦合,产生协同叠加的定向毛细管力,能够驱动高粘度渗出液由油凝胶富集区的疏水表面向水凝胶富集区的亲水表面发生定向迁移并抗回流。本发明的油水凝胶敷料通过异质相分布浓度梯度以及通道内壁润湿性梯度的设计,能够主动应对高粘度(高蛋白)渗出液挑战,不仅能高效疏通并清除这种粘性液体,防止液体在创面滞留,彻底解决传统敷料易堵塞、导致创周浸渍的难题,还能通过一体式的油水凝胶复合基质体的结构设计,克服层间剥离与脱落的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894547A_ABST
    Figure CN122894547A_ABST
Patent Text Reader

Abstract

The present application relates to an oil-water gel dressing, a forming die and a preparation method, and belongs to the technical field of medical devices. The oil-water gel dressing of the present application comprises an integrated oil-water gel composite matrix body, which is composed of a hydrogel-rich region, an oil-water two-phase transition region and an oil gel-rich region arranged in turn along the thickness direction, and presents a continuously changing phase distribution; a plurality of conical microchannels are provided in the oil-water gel composite matrix body for driving the directional migration of high-viscosity exudate from the oil gel-rich region towards the hydrogel-rich region. Through the design of heterogeneous phase distribution concentration gradient and channel inner wall wettability gradient, not only can the viscous liquid be efficiently dredged and removed, preventing the liquid from stagnating on the wound surface, but also the problem of easy clogging of traditional dressings leading to impregnation around the wound can be completely solved, and through the structural design of the integrated oil-water gel composite matrix body, the problems of interlayer peeling and falling off can be overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical device technology, specifically to an oil-water gel dressing, a molding die, and a preparation method. Background Technology

[0002] Wound exudate management is a core aspect of wound healing, and its failure is the leading cause of delayed healing. This problem is particularly pronounced in chronic ulcers such as diabetic foot ulcers and burns. These wounds not only have large amounts of exudate but also exhibit high viscosity due to their high content of protein, necrotic tissue, and cell debris. This abnormally viscous fluid easily accumulates in the wound cavity, clogging the absorbent pores of traditional dressings, causing a sharp decline in their absorbency and leading to leakage and peri-wound maceration. Furthermore, it provides a highly protected colonization environment for microorganisms, significantly increasing the risk of infection. Infection, in turn, triggers a more severe inflammatory response, producing even more high-viscosity exudate, creating a vicious cycle that is difficult to break.

[0003] The FHC (Fluid-Handling Capacity) of wound dressings is influenced by the characteristics of the inflowing exudate (such as composition, viscosity, and pH) as well as the dressing material and structure. Traditional absorbent dressings, such as polyurethane foam dressings, typically contain absorbable foam components and adhesive edges to achieve exudate absorption and mechanical protection. The interior of polyurethane foam dressings is not entirely composed of hydrophilic polyurethane foam material. A typical multilayer composite foam dressing consists of the following components: a wound contact layer (containing adhesive edges), a hydrophilic foam layer made of semi-permeable open-cell polyurethane foam, and a protective membrane (which can be impregnated with antibacterial agents to prevent bacterial contamination and liquid evaporation). The hydrophilic foam layer in the foam dressing includes an initial absorbent layer and a superabsorbent layer, as well as a diffusion layer located between the initial absorbent layer and the superabsorbent layer. This diffusion layer transports exudate from the initial absorbent layer to the superabsorbent layer, preventing it from flowing back to the wound or surrounding tissue.

[0004] However, the porous structure of polyurethane foam dressings is insufficient in its capillary absorption or transport capacity to drive rapid penetration and diffusion of high-viscosity liquids, making it prone to pore blockage and resulting in significant liquid retention at the dressing-wound interface. Furthermore, these multi-layered composite foam dressings are typically constructed through multiple physical lamination processes, resulting in weak bonding between layers. After absorbing liquid, the mismatch in swelling rates between layers easily leads to interlayer peeling and detachment, causing product failure. The detached material fragments can also become new sources of foreign body infection. Summary of the Invention

[0005] To address the above problems, the present invention provides an oil-water gel dressing, a molding die, and a preparation method.

[0006] The oil-water gel dressing of the present invention, through the design of heterogeneous phase distribution concentration gradient and channel inner wall wettability gradient, can actively cope with the challenge of high viscosity exudate. It can not only efficiently unclog and remove this viscous liquid, creating a dynamic and balanced suitable microenvironment for the wound, but also overcome the defects of existing technologies that are ineffective and passive in managing high viscosity exudate. Furthermore, through the structural design of the integrated oil-water gel composite matrix, it can overcome the problems of interlayer peeling and shedding.

[0007] The oil-hydrogel dressing of the present invention has a one-way fluid guiding function. The oil-hydrogel dressing of the present invention constructs an asymmetric hydrophilic and hydrophobic interface and a regular truncated conical microchannel in the molding die, which can simultaneously realize the active directional removal of high viscosity exudate and the active prevention and control of wound infection.

[0008] To achieve the above objectives, the technical solution of the present invention is as follows.

[0009] The first aspect of this invention provides an oil-hydrogel dressing, comprising an integral oil-hydrogel composite matrix. The oil-hydrogel composite matrix is ​​composed of a hydrogel-rich region, an oil-water two-phase transition region, and an oil-gel-rich region arranged sequentially along the thickness direction, exhibiting a continuously changing phase distribution. The oil-hydrogel composite matrix contains a plurality of conical microchannels that penetrate the hydrogel-rich region and the oil-gel-rich region, and the pore walls of the conical microchannels are formed of hydrogel. The pore size of the conical microchannels gradually decreases in the direction from the oil-gel-rich region to the hydrogel-rich region, thereby driving the directional migration of high-viscosity exudate in the direction from the oil-gel-rich region to the hydrogel-rich region.

[0010] The oil-hydrogel dressing of the present invention is a composite matrix with unidirectional fluid guiding function, which can effectively remove exudates including high-viscosity, high-solids-content fluids. The composite matrix is ​​composed of a hydrophilic hydrogel phase and a hydrophobic oleogel phase through an interpenetrating molecular network, and is a one-piece molded structure.

[0011] The composite matrix of this invention exhibits a varying phase distribution along the axial direction of the tapered pores, from largest to smallest diameter. The bottom surface of the large-diameter pores is composed of oleogel, while the pore walls and upper surface are composed of hydrogel. The overall internal structure is an oil-water two-phase composite structure.

[0012] The composite matrix contains multiple vertically penetrating, truncated cone-shaped microchannels. As the phase distribution changes, the deep coupling of the geometric structure and asymmetric wettability forms a strong capillary force in the microchannels, driving the high-viscosity exudate to migrate directionally from the lower surface (hydrophobic oleogel, large pore size) to the upper surface and resisting backflow.

[0013] The lower surface of the composite matrix is ​​constructed from a hydrophobic oleogel phase; the upper surface of the composite matrix is ​​constructed from a hydrophilic hydrogel phase; the first surface is a hydrophilic surface with a static water contact angle of less than 60°, and the second surface is a hydrophobic surface with a static water contact angle of greater than 110°, in order to promote the initial wetting of high-viscosity exudate, prevent liquid backflow, and enhance release to the external environment.

[0014] This invention utilizes the asymmetric geometry of microchannels and the wettability gradient of the microchannel inner wall to form a synergistic capillary force system, which drives the directional migration of high-viscosity exudate from hydrophobic to hydrophilic surfaces and resists backflow. The hydrophilic hydrogel phase contains a structural antibacterial polymer network, in which antibacterial functional groups are inherently distributed on the polymer backbone through covalent bonds to avoid uncontrolled leaching of antibacterial components.

[0015] Preferably, the two sides of the conical microchannel are a hydrophilic surface and a hydrophobic surface, respectively; the hydrophilic surface is located in the hydrogel-rich region and is formed by hydrogel; the hydrophobic surface is located in the oleogel-rich region and is formed by oleogel; the static water contact angle of the hydrophilic surface is less than 60° to promote the initial wetting of high-viscosity exudate; the static water contact angle of the hydrophobic surface is greater than 110° to prevent liquid backflow and enhance release to the external environment.

[0016] Preferably, the continuously changing phase distribution is along the direction of directional migration of the high-viscosity exudate, with the mass fraction of oleogel gradually decreasing and the mass fraction of hydrogel gradually increasing; the pore size of the conical microchannel on the hydrophobic surface is 0.5 mm to 2 mm; the pore size of the conical microchannel on the hydrophilic surface is 0.1 mm to 1 mm, and the pore size of the conical microchannel on the hydrophilic surface is smaller than the pore size of the conical microchannel on the hydrophobic surface; and the center distance between adjacent conical microchannels is 3 mm to 7 mm.

[0017] More preferably, the diameter of the conical microchannel on the hydrophobic surface is 1.25 mm; the diameter of the conical microchannel on the hydrophilic surface is 0.75 mm; and the center-to-center distance between adjacent conical microchannels is 5 mm.

[0018] Preferably, the oil-hydrogel composite matrix is ​​formed by in-situ cross-linking polymerization and curing of the oil-hydrogel prepolymer at the oil-water interface due to the surface tension difference, which induces microphase separation of the oil gel and hydrogel. The resulting structure consists of an integrated membrane structure composed of a hydrogel enrichment region, an oil-water transition region, and an oil gel enrichment region.

[0019] Preferably, the oil-hydrogel prepolymer is obtained by mixing an oil-hydrogel prepolymer and a hydrogel prepolymer; the hydrogel prepolymer is obtained by mixing raw materials with the following mass fractions: The composition consists of 10%–20% hydrogel monomer, 0.02%–0.05% first photoinitiator, 0.02%–0.05% first crosslinking agent, and the remainder is water, totaling 100%.

[0020] The oleogel prepolymer solution is obtained by mixing the following raw materials in the indicated mass fractions: The second photoinitiator is 0.02% to 0.05%, the second crosslinking agent is 0.05% to 1%, and the remainder is oleogel monomer, totaling 100%.

[0021] Preferably, the hydrogel monomer is selected from at least one of hydroxyethyl methacrylate, acryloyloxyethyltrimethylammonium chloride, methacryloyloxyethylhexadecyldimethylammonium bromide, methacrylated alginate, methacrylated gelatin, methacrylated chitosan, and polyvinyl alcohol. The oleogel monomer is lauryl methacrylate. Both the first and second photoinitiators are 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone; the first crosslinking agent is nano-clay sheets and / or N,N-methylenebisacrylamide; and the second crosslinking agent is ethylene glycol dimethacrylate.

[0022] Preferably, the mass ratio of oleogel prepolymer to hydrogel prepolymer is 1:2 to 5.

[0023] Preferably, the hydrogel prepolymer is obtained by mixing the following raw materials in the indicated mass fractions: Hydroxyethyl methacrylate 10%, Acryloyloxyethyltrimethylammonium chloride 5%, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone 0.05%, N,N-methylenebisacrylamide 0.03%, and deionized water 84.92%, totaling 100%.

[0024] The oleogel prepolymer is obtained by mixing the following raw materials in the indicated mass fractions: Lauryl methacrylate 98.95%, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone 0.05% and ethylene glycol dimethacrylate 1%, totaling 100%.

[0025] A second aspect of the present invention provides a molding die for preparing the oil-hydrogel dressing described in the first aspect; the molding die includes a hydrophilic template and a microstructure template, wherein the hydrophilic template and the microstructure template are combined to form a closed mold cavity; the surface of the hydrophilic template has a first hydrophilic modification layer; a plurality of conical mold cores are disposed on the microstructure template, the geometric shapes of the conical mold cores being complementary to those of the conical microchannels; the surface of each conical mold core has a second hydrophilic modification layer; and the bottom of the microstructure template has a hydrophobic surface layer.

[0026] In this invention, the hydrophilic template and the micron-structured template are combined to form a closed mold cavity; after injecting a homogeneous oil-water gel prepolymer, the oil-water gel prepolymer is induced to undergo phase separation along the pore size direction by the difference in surface tension, thereby forming a heterogeneous oil-water gel composite matrix in situ.

[0027] Preferably, the water contact angle of the first hydrophilic modified layer is 0° to 60°; the water contact angle of the second hydrophilic modified layer is 0° to 60°; and the water contact angle of the hydrophobic surface layer is 120° to 170°.

[0028] Preferably, the micron-structured template is made of at least one of a material with high thermal conductivity (titanium alloy TC4), hard aluminum, or chromium zirconium copper, in order to achieve rapid heat transfer and uniform polymerization during the photopolymerization manufacturing process.

[0029] Both the first hydrophilic modification layer of the hydrophilic template and the second hydrophilic modification layer of the microstructure template are formed by hydroxyl modification, coating with polyvinyl alcohol, coating with polydopamine, or plasma hydrophilic treatment.

[0030] The hydrophobic surface layer of the micron-structured template is formed by modifying the surface of a metal substrate with fluorosilane or silane, or by coating it with polytetrafluoroethylene, silane coupling agent or fluorosilicone resin, to form a hydrophobic surface layer with a micro-nano composite structure.

[0031] Preferably, the hydrophilic template uses a transparent substrate, such as a transparent resin substrate or a transparent glass sheet; its surface has a superhydrophilic modified layer. The metal substrate of the micron-structured template is a titanium alloy base plate, and its bottom has a hydrophobic surface layer.

[0032] A third aspect of this invention provides a method for preparing an oil-water gel dressing, comprising the following steps: An oil-hydrogel prepolymer containing hydrogel monomers and oleogel monomers is prepared; the oil-hydrogel prepolymer is injected into the molding mold described in the second aspect, so that the conical mold core is immersed in the oil-hydrogel prepolymer; after standing, the oil-hydrogel prepolymer undergoes in-situ directional phase separation by utilizing the hydrophilicity-hydrophobicity difference of the inner surface of the molding mold; the molding mold containing the oil-hydrogel prepolymer is irradiated with ultraviolet light at an ambient temperature of 0℃~40℃ to induce in-situ crosslinking polymerization and solidification, locking the phase separation state; after demolding, an oil-hydrogel dressing with a continuous phase distribution concentration gradient and a channel inner wall wettability gradient is obtained.

[0033] Compared with the prior art, the advantages of the present invention are as follows: 1. The oil-hydrogel dressing of the present invention utilizes the wettability gradient of the inner wall of the conical microchannel and has a continuously varying phase distribution along the thickness direction of the oil-hydrogel composite matrix. Through the deep coupling of the geometry of the conical microchannel and the continuous wettability gradient of the inner wall of the conical microchannel, a synergistic superposition of directional capillary forces is generated, which can drive high-viscosity exudate to migrate directionally from the hydrophobic surface of the oil gel-rich area to the hydrophilic surface of the hydrogel-rich area and resist backflow. The oil-hydrogel dressing of the present invention, through the design of heterogeneous phase distribution concentration gradient and channel inner wall wettability gradient, can actively cope with the challenge of high-viscosity (high-protein) exudate. It can not only efficiently unclog and remove this viscous liquid and prevent liquid from stagnating on the wound surface, but also completely solve the problems of easy clogging and peri-wound maceration of traditional dressings. Furthermore, through the structural design of the integrated oil-hydrogel composite matrix, it can overcome the problems of interlayer peeling and shedding.

[0034] 2. This invention abandons traditional multiple casting, freeze-thaw, or physical lamination processes, and achieves exceptional structural stability in the prepared oil-hydrogel dressing through a one-step in-situ molding process. Using a specially designed wettable molding mold, this invention utilizes the spontaneous phase separation and in-situ photocuring of the oil-hydrogel prepolymer to freeze a perfect gradient structure in a single step. The layers are connected by a molecular-level interpenetrating polymer network, preventing delamination even during the absorption of high-viscosity liquids and swelling, significantly improving the safety and reliability for clinical use. Attached Figure Description

[0035] Figure 1 The images shown are scanning electron microscope (SEM) images of the upper layer, lower layer, and conical microchannels of the oil-hydrogel dressings obtained in Example 1 and Comparative Example 1 of the present invention. Specifically, (a1) and (a2) are SEM images of the upper layer of the oil-hydrogel dressing of Example 1; (a3) ​​and (a4) are SEM images of the lower layer of the oil-hydrogel dressing of Example 1; (a5) and (a6) are SEM images of the conical microchannels of the oil-hydrogel dressing of Example 1; (b1) and (b2) are SEM images of the upper layer of the oil-hydrogel dressing of Comparative Example 1; (b3) and (b4) are SEM images of the lower layer of the oil-hydrogel dressing of Comparative Example 1; and (b5) and (b6) are SEM images of the conical microchannels of the oil-hydrogel dressing of Comparative Example 1.

[0036] Figure 2 The images show the initial static contact angles of the hydrogel dressing obtained in Example 1 and Comparative Example 1. Specifically, (a) shows the initial static contact angle of the hydrogel-rich region in Example 1; (b) shows the initial static contact angle of the hydrogel-rich region in Example 1; (c) shows the initial static contact angle of the hydrogel-rich region in Comparative Example 1; and (d) shows the initial static contact angle of the hydrogel-rich region in Comparative Example 1.

[0037] Figure 3The diagrams show the dynamic contact angle changes of the oil-water gel dressing obtained in Example 1 of the present invention and the comparative dressings obtained in Comparative Examples 1 to 2. Among them, (a) is the dynamic contact angle change of the comparative dressing from 0s to 10s; (b) is the dynamic contact angle change of the comparative dressing from 0s to 0.05s.

[0038] Figure 4 This describes the process of a large amount of liquid passing through both sides of Embodiment 1 and Comparative Examples 1 to 2 of the present invention. In the figures, (a1) to (a3) ​​are the liquid flow process diagrams of the oil-water gel dressing of Example 1 from the hydrophobic surface to the hydrophilic surface from 0s to 2s; (a4) to (a6) are the liquid flow process diagrams of the oil-water gel dressing of Example 1 from the hydrophobic surface to the hydrophilic surface from 0s to 20s; (b1) to (b3) are the liquid flow process diagrams of the oil-water gel dressing of Comparative Example 1 from the hydrophobic surface to the hydrophilic surface from 0s to 2s; (b4) to (b6) are the liquid flow process diagrams of the oil-water gel dressing of Comparative Example 1 from the hydrophobic surface to the hydrophilic surface from 0s to 20s; (c1) to (c3) are the liquid flow process diagrams of the oil-water gel dressing of Comparative Example 2 from the hydrophobic surface to the hydrophilic surface from 0s to 2s; and (c4) to (c6) are the liquid flow process diagrams of the oil-water gel dressing of Comparative Example 2 from the hydrophobic surface to the hydrophilic surface from 0s to 20s.

[0039] Figure 5 These are diagrams illustrating the single-drop directed water-directing process of the oil-water gel dressing in Example 1 and Comparative Examples 1 to 2 of the present invention. Specifically, (a1) to (a4) are diagrams illustrating the single-drop directed water-directing process of the oil-water gel dressing in Example 1 from 0 ms to 100 ms; (b1) to (b4) are diagrams illustrating the single-drop directed water-directing process of the oil-water gel dressing in Comparative Example 1 from 0 ms to 100 ms; and (c1) to (c4) are diagrams illustrating the single-drop directed water-directing process of the oil-water gel dressing in Comparative Example 2 from 0 ms to 100 ms.

[0040] Figure 6 The images show the bacterial counts of Example 1 and Comparative Example 1 after incubation in the antibacterial performance test. Specifically, (a1) shows the bacterial count of the oil-water gel dressing of Example 1 before incubation; (a2) shows the bacterial count of the oil-water gel dressing of Example 1 after incubation; (b1) shows the bacterial count of the oil-water gel dressing of Comparative Example 1 before incubation; (b2) shows the bacterial count of the oil-water gel dressing of Comparative Example 1 after incubation; (c1) shows the bacterial count of the blank control before incubation; and (c2) shows the bacterial count of the blank control after incubation.

[0041] Figure 7The images show the wound healing results of the oil-water gel dressings of Example 1 and Comparative Examples 1-2 in a diabetic mouse wound model. Specifically, (a1)-(a7) are comparison images of wound healing of the oil-water gel dressing of Example 1 from 0 to 12 days; (b1)-(b7) are comparison images of wound healing of the oil-water gel dressing of Comparative Example 1 from 0 to 12 days; (c1)-(c7) are comparison images of wound healing of the oil-water gel dressing of Comparative Example 2 from 0 to 12 days; and (d1)-(d7) are comparison images of wound healing of the blank control from 0 to 12 days. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0043] The permeability of each dressing layer to high-viscosity exudate is closely related to the microstructure of the material components. The capillary absorption or transport capacity of liquid inside a specific dressing essentially depends on the characteristics of the dressing material.

[0044] In a first aspect, the present invention provides an oil-hydrogel dressing; the core of the oil-hydrogel dressing lies in: an integrally molded composite matrix composed of a hydrophilic hydrogel phase and a hydrophobic oleogel phase through an interpenetrating molecular network, possessing unidirectional fluid guiding function. Through an integrated in-situ molding process induced by a molding die, a phase distribution gradient and an asymmetric conical microchannel structure are constructed, thereby achieving directional transport of high-viscosity exudate and dynamic balance of the wound microenvironment. The composite matrix has a continuously varying phase distribution along its thickness direction, specifically characterized as follows:

[0045] Gradient Continuous Phase Distribution: The composite matrix exhibits a decreasing hydrogel concentration gradient from the hydrophilic surface (backing drainage layer) to the hydrophobic surface (wound contact layer), and an increasing oleogel concentration gradient. This phase distribution gradient structure is not a simple multilayer physical stacking, but rather a continuous transition spontaneously formed during a single polymerization process through in-situ induced phase separation. The middle layer is a mixed transition region where hydrogel and oleogel interpenetrate, seamlessly connecting the upper and lower layers to form a mechanically extremely stable whole, fundamentally eliminating the risk of interlayer delamination after absorbing high-viscosity liquids.

[0046] Asymmetric surface wettability: The hydrophobic surface (wound contact layer) is enriched with hydrophobic oleogel, and its static water contact angle is configured to be greater than 110°. Its strong hydrophobicity and low surface energy properties can effectively push the high-viscosity liquid that has gathered here into the dressing and fundamentally prevent the backflow of the high-viscosity liquid that has been absorbed, effectively protecting the skin around the wound from maceration.

[0047] The hydrophilic surface (backing drainage layer) is enriched with hydrophilic hydrogel, and its static water contact angle is configured to be less than 60°. Its strong hydrophilicity can quickly disrupt the surface tension of the permeated liquid, enabling rapid spreading and evaporation of the liquid, or transferring it to the outer auxiliary absorption pad.

[0048] A synergistic dual-driven microchannel system: The composite matrix contains multiple vertically penetrating truncated conical microchannels. Not only do these conical microchannels possess asymmetrical geometry—with smaller opening diameters on hydrophilic surfaces and larger opening diameters on hydrophobic surfaces—but more importantly, due to the continuous phase gradient within the composite matrix itself, this asymmetrical geometry and the truncated conical microchannels superimpose to form a synergistic capillary force system. This microchannel system generates an extremely strong directional Laplace pressure difference within the conical microchannels, overcoming the significant viscous resistance of high-viscosity fluids and providing a powerful and continuous active upward suction force for high-viscosity exudates.

[0049] Long-lasting structural antibacterial properties: The hydrogel constituting the hydrophilic phase of this invention is a "structural antibacterial polymer network" in which antibacterial functional groups are inherently distributed on the polymer backbone through covalent bonds. This design provides dressings with contact-based, long-lasting, and non-resistant bulk antibacterial capabilities without relying on any free antibacterial agents, avoiding the toxicity problems caused by uncontrolled leaching of traditional antibacterial components.

[0050] Specifically, the hydrogel framework of this invention is itself polymerized from antibacterial monomers, eliminating the need for external free antibacterial agents and constructing an intrinsic structural long-lasting antibacterial barrier. This structural antibacterial effect is not only long-lasting and does not produce burst-release toxicity, but it is also less likely to induce bacterial resistance. Combined with the characteristic of rapidly evacuating high-viscosity exudate, it completely destroys the moist, nutrient-rich environment on which bacteria and biofilms depend for survival, thus blocking the vicious cycle of wound infection from both physical and chemical dimensions.

[0051] The naturally formed hydrophilic and hydrophobic gradient network of this invention enables the construction of an intelligent dual-drug delivery and bidirectional regulatory microenvironment, creating an ideal platform for stable loading of hydrophilic / hydrophobic drugs in separate zones. The hydrophobic contact layer resists backflow and can sustainably release anti-inflammatory and analgesic drugs, while the hydrophilic outer layer strongly absorbs liquid and can release water-soluble healing-promoting factors. Together, they create a dynamically balanced, spatiotemporally controllable optimal microenvironment for the repair of complex chronic wounds.

[0052] The oil-hydrogel dressing of the present invention comprises an integral oil-hydrogel composite matrix, wherein the oil-hydrogel composite matrix is ​​composed of a hydrogel-rich region, an oil-water two-phase transition region, and an oil-gel-rich region arranged sequentially along the thickness direction, and exhibits a continuously changing phase distribution; the oil-hydrogel composite matrix is ​​provided with a plurality of conical microchannels, the conical microchannels penetrating the hydrogel-rich region and the oil-gel-rich region, and the pore walls of the conical microchannels are formed of hydrogel; the pore size of the conical microchannels gradually decreases in the direction from the oil-gel-rich region to the hydrogel-rich region, for driving the high-viscosity exudate to migrate directionally in the direction from the oil-gel-rich region to the hydrogel-rich region.

[0053] The oil-hydrogel composite matrix of the present invention comprises a hydrophilic surface (backing drainage layer, hydrogel enrichment area), a middle mixed transition area, and a hydrophobic surface (wound contact layer, oleogel enrichment area) that are smoothly transitioned in sequence.

[0054] In a preferred embodiment, the two sides of the conical microchannel are a hydrophilic surface and a hydrophobic surface, respectively; the hydrophilic surface is located in the hydrogel-rich region and is formed by hydrogel; the hydrophobic surface is located in the oleogel-rich region and is formed by oleogel; the static water contact angle of the hydrophilic surface is less than 60° to promote the initial wetting of the high-viscosity exudate; the static water contact angle of the hydrophobic surface is greater than 110° to prevent liquid backflow and enhance release to the external environment.

[0055] The continuously changing phase distribution is along the direction of directional migration of the high-viscosity exudate, with the mass fraction of oleogel gradually decreasing and the mass fraction of hydrogel gradually increasing.

[0056] In a preferred embodiment, the oil-hydrogel dressing contains an array of truncated conical microchannels penetrating the oil-hydrogel composite matrix. The geometry of these conical microchannels is precisely designed: the opening diameter of the microchannels on the hydrophilic surface (backing drainage layer, hydrogel-rich area) is 0.1 mm to 1 mm, the opening diameter on the hydrophobic surface (wound contact layer, oil-hydrogel-rich area) is 0.5 mm to 2 mm, and the central axis spacing between adjacent conical microchannels is 3 mm to 7 mm; more preferably, the opening diameter of the microchannels on the hydrophilic surface is 0.75 mm, the opening diameter on the hydrophobic surface is 1.25 mm, and the central distance between adjacent conical microchannels is 5 mm. These specific geometric parameters are the result of optimization for the rheological behavior of high-viscosity non-Newtonian fluids. This asymmetric channel structure can generate a Laplace pressure difference of 0.5 kPa to 5 kPa at the liquid-gas interface, providing a continuous directional driving force for high-viscosity exudates.

[0057] The mechanism of action is as follows: Structural antibacterial and hydrophilic mechanism (hydrophilic surface): The hydrophilic surface is a hydrogel-rich region composed of monomers with inherent antibacterial properties. For example, monomers containing quaternary ammonium groups or chitosan are used, whose polymer backbone carries a positive charge (-NH3) in the environment. + The polymer can strongly adsorb onto the negatively charged bacterial cell membrane through electrostatic interactions, directly disrupting the integrity of the membrane structure. Furthermore, specific functional groups (such as amino and hydroxyl groups) on the polymer chain can efficiently chelate trace metal ions essential for bacterial growth, indirectly inhibiting bacterial metabolism. This region exhibits superhydrophilicity (preferably with a water contact angle less than 60°) because the polymer's three-dimensional network contains numerous hydrophilic groups. When water comes into contact, "hydration" occurs through hydrogen bonds and ion-dipole interactions, locking a large number of water molecules within the network. Specifically, the hydrogel monomer is selected from at least one of hydroxyethyl methacrylate, acryloyloxyethyltrimethylammonium chloride, methacryloyloxyethylhexadecyldimethylammonium bromide, methacrylated alginate, methacrylated gelatin, methacrylated chitosan, and polyvinyl alcohol.

[0058] Anti-reflux and hydrophobic mechanism (hydrophobic surface): The hydrophobic surface is an oleogel-rich region, mainly composed of monomers rich in hydrophobic groups such as long-chain alkanes. The nonpolar nature of the hydrocarbon chains results in only very weak van der Waals forces between the surface and water molecules, preventing the formation of hydrogen bonds. Water molecules are more likely to be "repelled" by this surface, macroscopically manifested as a large water contact angle (preferably greater than 120°) and non-wetting properties, thus providing excellent anti-reflux and protection of the surrounding skin from maceration. Specifically, the oleogel monomer is lauryl methacrylate.

[0059] Intermediate layer mixing transition zone: In this zone, hydrogel and oleogel are distributed in a bicontinuous phase, seamlessly connecting the upper and lower layers through molecular-level penetration, completely avoiding the interlayer delamination problem of traditional composite dressings after liquid absorption.

[0060] Preferably, the structural antibacterial hydrogel of the present invention is polymerized from monomers possessing both hydrophilicity and antibacterial properties, selected from acryloyloxyethyltrimethylammonium chloride (DAC), methacryloyloxyethylhexadecyldimethylammonium bromide (HDMA), or chitosan-g-trimethylallylammonium chloride, etc. The oleogel is selected from lauryl methacrylate (LMA), vegetable oil-based oleogels, or polymer oleogels, etc.

[0061] Furthermore, the dressing can be loaded with dual active ingredients to achieve spatiotemporally controllable synergistic therapy: the hydrophilic hydrogel phase is loaded with water-soluble active ingredients (such as water-soluble antibiotics and growth factors), while the hydrophobic oleogel phase is loaded with lipid-soluble drugs (such as anti-inflammatory analgesics such as ibuprofen).

[0062] Secondly, to prepare the aforementioned dressing, this invention provides a molding die utilizing surface tension differences. The molding die guides longitudinal phase separation of the precursor solution by creating an asymmetric physicochemical interface environment. The molding die comprises a hydrophilic template and a micron-structured template, wherein the hydrophilic template and the micron-structured template are combined to form a closed mold cavity. The surface of the hydrophilic template has a first hydrophilic modification layer. Multiple conical mold cores are disposed on the micron-structured template, the geometry of which is complementary to that of the conical microchannels. The surface of each conical mold core has a second hydrophilic modification layer. The bottom of the micron-structured template has a hydrophobic surface layer.

[0063] In this invention, the hydrophilic template and the micron-structured template are combined to form a closed mold cavity; after injecting a homogeneous oil-water gel prepolymer, the oil-water gel prepolymer is induced to undergo phase separation along the pore size direction by the difference in surface tension, thereby forming a heterogeneous oil-water gel composite matrix in situ.

[0064] Preferably, the water contact angle of the first hydrophilic modified layer is 0° to 60°; the water contact angle of the second hydrophilic modified layer is 0° to 60°; and the water contact angle of the hydrophobic surface layer is 120° to 170°.

[0065] Preferably, the micron-structured template is made of at least one of a material with high thermal conductivity (titanium alloy TC4), hard aluminum, or chromium zirconium copper, in order to achieve rapid heat transfer and uniform polymerization during the photopolymerization manufacturing process.

[0066] Both the first hydrophilic modification layer of the hydrophilic template and the second hydrophilic modification layer of the microstructure template are formed by hydroxyl modification, coating with polyvinyl alcohol, coating with polydopamine, or plasma hydrophilic treatment.

[0067] The hydrophobic surface layer of the micron-structured template is formed by modifying the surface of a metal substrate with fluorosilane or silane, or by coating it with polytetrafluoroethylene, silane coupling agent or fluorosilicone resin, to form a hydrophobic surface layer with a micro-nano composite structure.

[0068] The closed mold cavity of the present invention is configured such that, after the injection of a homogeneous oil-hydrogel prepolymer, no external mechanical force is required, and the homogeneous precursor solution can be induced to spontaneously undergo longitudinal directional phase separation solely by relying on the difference in hydrophilic and hydrophobic tension on the template surface.

[0069] Mold and Molding Mechanism: The closed cavity of the molding mold consists of a hydrophilic upper template assembly, a hydrophobic lower template, and an insulating frame. When a homogeneous oil-hydrogel prepolymer containing hydrogel monomers and oleogel monomers is injected into the closed cavity, the system undergoes directional phase separation without external mechanical force under the drive of asymmetric interfacial tension. The hydrophilic upper template assembly preferentially adsorbs and enriches hydrogel monomers through strong capillary forces and hydrogen bonding generated by its superhydrophilic surface (water contact angle 0°–60°); while the hydrophobic lower template selectively enriches oleogel monomers due to its extremely low surface energy (water contact angle 120°–170°). This spatial selectivity induces the spontaneous formation of a concentration gradient between the two components within the molding cavity. Subsequently, in-situ polymerization occurs under ultraviolet light irradiation, "instantly locking" this gradient state, ultimately obtaining a functional dressing with a precise and continuous concentration gradient and a regular microchannel inner wall wettability gradient.

[0070] Thirdly, the present invention provides a method for manufacturing an actively draining oil-water gel dressing using the above-mentioned molding die. The method includes the following steps:

[0071] Step 1: Prepare a homogeneous oil-hydrogel prepolymer containing hydrogel monomers and olegel monomers.

[0072] Step 2: Inject the homogeneous composite precursor solution into the closed mold cavity formed by the hydrophilic upper template assembly and the hydrophobic lower template, ensuring that the hydrophilic conical mold core is completely submerged.

[0073] Step 3: Allow the mixture to stand for a predetermined time. Utilize the extreme hydrophilicity-hydrophobicity difference between the upper and lower inner surfaces of the mold to drive in-situ directional phase separation of the composite precursor solution. At this time, hydrophilic monomers accumulate in the hydrophilic upper template (including the hydrophilic core), while hydrophobic monomers accumulate in the superhydrophobic lower template, forming a continuous transition in between.

[0074] Step 4: At room temperature (0℃ to 40℃), the mold is irradiated with ultraviolet light through a transparent upper template to initiate in-situ crosslinking polymerization and curing of the hydrogel and oleogel monomers. This step "instantly locks" the phase separation state, forming a concentration gradient in one step.

[0075] Step 5: Demolding, to obtain an oil-water gel dressing with a composite matrix having a continuous phase distribution concentration gradient and a microchannel inner wall wettability gradient in one step.

[0076] This invention's oil-hydrogel dressing achieves efficient management of high-viscosity exudate and precise control of the wound microenvironment through the synergistic effect of a three-layer gradient structure, conical microchannels, and a structural antibacterial mechanism. Regarding exudate management, this device establishes a complete directional fluid transport system: the bottom hydrophobic region effectively blocks fluid backflow through its low surface energy, preventing percutaneous skin maceration; the middle gradient transition region achieves smooth exudate conduction through a continuously changing hydrophilic-hydrophobic balance; and the upper superhydrophilic region rapidly captures and temporarily stores exudate through its three-dimensional network structure. Particularly noteworthy is the conical microchannels (0.75mm at the top / 1.25mm at the bottom) that run throughout the device. Their unique geometric shape generates a Laplace pressure difference, creating a low-resistance directional drainage path for high-viscosity exudate. The 5mm equidistant arrangement ensures both drainage uniformity and maintains the structural mechanical integrity. In terms of the antibacterial mechanism, this device overcomes the limitations of traditional dressings that rely on antibiotics or silver ions, employing a structural antibacterial design. The upper region generates a positively charged surface through covalently grafted quaternary ammonium salt groups, directly disrupting the integrity of bacterial cell membranes. Simultaneously, specific functional groups in the polymer network chelate essential metal ions for bacteria, synergistically inhibiting microbial growth through multiple pathways. This non-release antibacterial mechanism not only avoids drug resistance issues but also provides continuous and stable antibacterial protection. In terms of optimizing the wound healing environment, this device exhibits unique advantages: the upper hydrogel region maintains a suitable moist environment, promoting autolytic debridement; the lower oleogel region ensures good gas exchange; and the regular microchannel array establishes an efficient gas-liquid two-phase flow path. This multi-layered design provides an ideal microenvironment for wound healing, significantly promoting granulation tissue formation and epithelialization. Furthermore, the device's gradient structure design gives it excellent mechanical properties and biocompatibility, conforming to the contours of various body parts without causing mechanical stress to the wound. Its integrated structural design simplifies clinical procedures; the transparent microchannels facilitate wound observation, while the hydrophobic bottom layer effectively reduces tissue damage during wound replacement. In summary, the wound exudate management device of the present invention, through innovative structural design and material selection, effectively solves key technical challenges such as high-viscosity exudate removal, long-lasting antibacterial effect, and wound microenvironment regulation, providing an ideal solution for the treatment of complex wounds such as diabetic foot ulcers, burns, and pressure injuries. The inner surface of the mold includes a hydrophilic upper template assembly and a hydrophobic lower template; the hydrophilic upper template assembly and the hydrophobic lower template are arranged opposite to each other; the enrichment of the hydrogel monomers and oleogel monomers is induced by the hydrophilicity of the superhydrophilic upper template assembly and the hydrophobicity of the superhydrophobic lower template.

[0077] When an oil-hydrogel prepolymer containing hydrogel and oleogel monomers is injected into a closed molding system consisting of a hydrophilic upper template assembly and a hydrophobic lower template, directional phase separation occurs under the drive of asymmetric interfacial tension. The hydrophilic upper template assembly preferentially adsorbs hydrogel monomers through strong hydrogen bonding and capillary forces generated by its superhydrophilic surface (water contact angle less than 10°), while the hydrophobic lower template selectively enriches oleogel monomers through van der Waals forces due to its extremely low surface energy (water contact angle greater than 150°). This spatially selective induction based on significant surface energy differences leads to a controllable distribution of the two components within the molding cavity: a hydrogel monomer enrichment region forms in the conical micropillar region adjacent to the hydrophilic upper template assembly, and an oleogel monomer enrichment region forms on the surface region of the hydrophobic lower template. A mixed region with continuous component transition naturally forms between the two enrichment regions through molecular diffusion. The closed cavity composed of an insulating frame effectively blocks lateral heat exchange, ensuring that this interfacial induction process proceeds stably under isothermal conditions. This molding process does not require the application of an external field, and the concentration gradient formed can be effectively solidified in the subsequent UV polymerization process through the transparency of the hydrophilic template component, ultimately obtaining a functional dressing with a precise gradient structure and regular microchannels.

[0078] In some embodiments, the water contact angle of the hydrophilic upper template assembly is 0° to 60°.

[0079] In some embodiments, the water contact angle of the template under the hydrophobic structure is 120° to 170°.

[0080] Furthermore, the water contact angle of the hydrophilic upper template assembly is not greater than the water contact angle of the hydrogel-rich region; the water contact angle of the hydrophobic lower template is not less than the water contact angle of the oleogel-rich region.

[0081] In this invention, the hydrophilic upper template component can be made of existing hydrophilic materials, or its inner surface can be modified to be hydrophilic, so that the inner surface of the sidewall exhibits hydrophilicity.

[0082] Similarly, the hydrophobic lower template in this invention can be made of existing hydrophobic materials, or its inner surface can be hydrophobically modified to make the inner surface of the sidewall hydrophobic.

[0083] In some embodiments, the hydrogel monomer is selected from at least one of hydroxyethyl methacrylate, acryloyloxyethyltrimethylammonium chloride, methacryloyloxyethylhexadecyldimethylammonium bromide, methacrylated alginate, methacrylated gelatin, methacrylated chitosan, and polyvinyl alcohol.

[0084] In some embodiments, the oleogel monomer is lauryl methacrylate. Both the first and second photoinitiators are 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone; the first crosslinking agent is nano-clay flakes and / or N,N-methylenebisacrylamide; and the second crosslinking agent is ethylene glycol dimethacrylate.

[0085] In some embodiments, the oil-hydrogel prepolymer includes an aqueous phase and an oil phase; the aqueous phase includes a hydrogel prepolymer containing hydrogel monomers; the oil phase includes an oil-hydrogel prepolymer containing oleogel monomers; the hydrogel prepolymer includes hydrogel monomers, a first solvent, a first initiator, and a first crosslinking agent; the oleogel prepolymer includes oleogel monomers, a second initiator, and a second crosslinking agent.

[0086] In some embodiments, the hydrogel monomer, the first solvent, the first initiator and the first crosslinking agent are mixed to form a hydrogel prepolymer; the oleogel monomer, the second initiator and the second crosslinking agent are mixed to form an oleogel prepolymer; then the hydrogel prepolymer and the oleogel prepolymer are mixed and dispersed to form a stable emulsion.

[0087] The mass ratio of hydrogel prepolymer to olegel prepolymer can be 3:2.

[0088] In some embodiments, a stable mixed emulsion is obtained by ultrasonic dispersion after mixing the hydrogel prepolymer and the oleogel prepolymer. The ultrasonic dispersion interval frequency is exemplarily 0.5s to 2s, the ultrasonic dispersion time is exemplarily 1min to 5min, and the ultrasonic power is exemplarily 200W to 1000W. Here, the ultrasonic dispersion frequency is understood as the time interval between two adjacent ultrasonic dispersions. That is, in this invention, multiple intermittent ultrasonic dispersions are used to fully mix the hydrogel prepolymer and the oleogel prepolymer, wherein the multiple intermittent ultrasonic dispersions are: every 0.5s to 2s of ultrasonic dispersion, followed by a 0.5s to 2s pause. The ultrasonic dispersion time is 1min to 5min.

[0089] Ultrasonic dispersion can disperse oleogel monomers into fine particles, which are dispersed in the aqueous phase to form a stable emulsion. Under the influence of interface induction, hydrogel monomers and oleogel monomers can move to the corresponding interface, forming hydrogel monomer enrichment regions and oleogel monomer enrichment regions.

[0090] In some embodiments, the first solvent may be water, which may be any one of deionized water, ultrapure water, or pure water; the first initiator may be a photoinitiator, such as 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone; and the first crosslinking agent may be at least one of nano-clay sheets or N,N-methylenebisacrylamide.

[0091] In some embodiments, the second initiator is a photoinitiator, such as 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone; the second crosslinking agent may be at least one of ethylene glycol dimethacrylate.

[0092] In some embodiments, the mass ratio of oleogel prepolymer to hydrogel prepolymer is (1-2):(2-6).

[0093] In some embodiments, the hydrogel monomers are enriched on the surface of the hydrophilic upper template component and the oleogel monomers on the surface of the hydrophobic lower template component of the mold by interfacial induction. This includes: dropping an oil-hydrogel prepolymer between the hydrophilic upper template component and the hydrophobic lower template component, allowing it to stand, and allowing it to be enriched through interfacial induction. The preparation method further includes: curing. The curing includes: polymerizing the layered oil-hydrogel prepolymer under ultraviolet light for 1-4 hours to obtain a dressing.

[0094] The technical solution of the present invention will be further described below through specific embodiments. Unless otherwise specified, the methods described in the following embodiments are conventional methods; the reagents and materials described are commercially available unless otherwise specified.

[0095] Example 1 An oil-hydrogel dressing is prepared by injecting an oil-hydrogel prepolymer into a mold, followed by interfacial induction and polymerization under ultraviolet light irradiation to form a film structure consisting of hydrogel-rich regions, mixed regions, and oil-hydrogel-rich regions. The oil-hydrogel prepolymer is obtained by mixing an oil-hydrogel prepolymer and a hydrogel prepolymer at a mass ratio of 3:2.

[0096] The hydrogel prepolymer is prepared using hydroxyethyl methacrylate and acryloyloxyethyltrimethylammonium chloride as hydrogel monomers, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone as the first photoinitiator, N,N-methylenebisacrylamide as the first crosslinking agent, and deionized water as the solvent. The hydrogel prepolymer is obtained by mixing the following raw materials in the indicated mass fractions: Hydroxyethyl methacrylate 10%, Acryloyloxyethyltrimethylammonium chloride 5%, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone 0.05%, N,N-methylenebisacrylamide 0.03%, and deionized water 84.92%, totaling 100%.

[0097] The oleogel prepolymer is prepared by using lauryl methacrylate as the oleogel monomer, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone as the second photoinitiator, and ethylene glycol dimethacrylate as the second crosslinking agent. The oleogel prepolymer is obtained by mixing the following raw materials in the indicated mass fractions: Lauryl methacrylate 98.95%, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone 0.05% and ethylene glycol dimethacrylate 1%, totaling 100%.

[0098] The preparation method of the oil-water gel dressing includes the following steps: S1. Preparation of the hydrogel prepolymer: Hydroxyethyl methacrylate, acryloyloxyethyltrimethylammonium chloride, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, and N,N-methylenebisacrylamide were added to deionized water and stirred and dispersed for 60 min to form the hydrogel prepolymer.

[0099] Lauryl methacrylate, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, and ethylene glycol dimethacrylate are stirred and mixed evenly to form an oil gel prepolymer.

[0100] The hydrogel prepolymer and the oleogel prepolymer were mixed at a mass ratio of 3:2 and ultrasonically dispersed for 1 minute using a 600W cell disruptor to obtain the oleogel prepolymer.

[0101] S2. Interface Induction: The titanium alloy substrate was treated with plasma surface treatment equipment at 300W for 10 min, and then subjected to vapor phase modification with fluorosilane in an 80℃ oven for 8 h to obtain a hydrophobic titanium alloy substrate. The glass slide was treated with plasma surface treatment equipment at 300W for 10 min to obtain a hydrophilic glass slide.

[0102] A hydrophobic titanium alloy base plate is used as the lower template for the hydrophobic structure, and a hydrophilic glass sheet is used as the upper template for the structured hydrophilic structure. Then, a conical column on the hydrophobic titanium alloy base plate is treated with plasma surface treatment equipment at 300W for 10 minutes to create a hydrophilic conical column. A gasket is used as the sidewall to form the mold. The water contact angle of the hydrophobic titanium alloy base plate is 90°–160°; the water contact angle of the hydrophilic glass sheet is 0°–60°.

[0103] The oil-hydrogel prepolymer was added between the hydrophilic glass slide and the hydrophobic titanium alloy base plate and allowed to stand for 5 minutes to obtain the interface-induced oil-hydrogel prepolymer.

[0104] S3. Photopolymerization: Using ultraviolet light to irradiate the mold, the monomers in the interface-induced oil-hydrogel prepolymer solution are polymerized to form a film structure composed of hydrogel-enriched region, mixed region and oil-gel-enriched region, and the oil-hydrogel dressing is obtained, denoted as sample A.

[0105] Comparative Example 1 Compared to Example 1, Comparative Example 1 used an unmodified glass sheet as the first wall panel of the mold, with a water contact angle of 30°, and an unmodified titanium alloy base plate as the second wall panel, with a water contact angle of 40°. The other raw materials and steps were the same as in Example 1, resulting in an oil-water gel dressing, denoted as Sample B.

[0106] Comparative Example 2 Compared to Example 1, Comparative Example 2 uses a metal base plate with an array of cylindrical columns on a titanium alloy base plate as the second wall plate. The other raw materials and steps are the same as in Example 1, resulting in an oil-water gel dressing, denoted as Sample C.

[0107] Test 1: Microstructure analysis of oil-water gel dressing.

[0108] The microstructures of sample A from Example 1 and sample B from Comparative Example 1 were characterized using scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown. From Figure 1 As can be seen from the above, the hydrogel-rich area of ​​the oil-hydrogel dressing obtained in Example 1 has a porous structure, and the hydrogel particles are distributed in the porous structure; the conical microchannels that run through the hydrogel-rich area, the oil-gel-rich area and the mixed area are also hydrogel-rich areas, and the hydrogel particles are accumulated on the surface of the conical microchannels; the oil gel monomers in the oil-gel-rich area are cross-linked and dense on the surface, forming a blocky oil gel.

[0109] In addition, the microstructure of the oil-hydrogel dressing obtained in Comparative Example 1 was characterized, such as... Figure 1 As shown. From Figure 1 It can be seen that the oil-hydrogel dressing obtained in Comparative Example 1 has no fixed structure. The upper hydrogel-rich area, the oil-rich area, and the conical microchannels that run through the hydrogel-rich area, the oil-rich area, and the mixed area are all in a mixed state of hydrogel and oil gel.

[0110] Test 2: Contact Angle Test.

[0111] The initial static contact angle and dynamic contact angle of water were measured on the surfaces of the hydrogel-rich regions and olegel-rich regions of sample A obtained in Example 1, sample B obtained in Comparative Example 1, and sample C obtained in Comparative Example 2, respectively, using a contact angle meter. The results are as follows: Figure 2 and Figure 3 As shown.

[0112] from Figure 2It can be seen that the initial contact angle of the hydrogel-enriched region surface of sample A obtained in Example 1 is 30.1±1.5°, and the initial contact angle of the oleogel-enriched region surface of sample B is 122.0±2.2°; the initial contact angle of the hydrogel-enriched region surface of sample B is 61.9±2.1°, and the initial contact angle of the oleogel-enriched region surface of sample B is 58.9±1.9°. It is evident that the hydrophilicity and hydrophobicity of the hydrogel-enriched and oleogel-enriched regions of sample A obtained in Example 1 are significantly different, forming distinct hydrogel-enriched and oleogel-enriched regions. In contrast, sample B, which did not undergo interface induction, did not form distinct hydrogel-enriched and oleogel-enriched regions.

[0113] from Figure 3 As can be seen, with the extension of time, sample A can absorb water completely within 0.01s, while sample C requires 0.03s to achieve a similar absorption effect. Sample B does not show obvious water absorption after 10s. It can be seen that directional through-holes can optimize the water absorption performance of dressings, and conical microchannels can accelerate water absorption more than straight cylindrical microchannels.

[0114] Test 3: Observation of the fluid transfer process.

[0115] A total of 1 mL of liquid was continuously added dropwise to the surfaces of sample A obtained in Example 1, sample B obtained in Comparative Example 1, and sample C obtained in Comparative Example 2. The liquid transfer process was observed from above, and the results are as follows: Figure 4 As shown.

[0116] from Figure 4 It can be seen that when liquid is dropped onto the surface of the oleogel-rich region of sample A obtained in Example 1 and sample C obtained in Comparative Example 2, the liquid can spontaneously pass through the oleogel layer and there is no liquid residue on the surface. However, when liquid is added to the surface of the oleogel-rich region of sample B obtained in Comparative Example 1, the liquid cannot pass through the oleogel layer and spread on the surface.

[0117] When liquid is dropped onto the surface of the hydrogel-rich region of sample A obtained in Example 1, sample B obtained in Comparative Example 1, and sample C obtained in Comparative Example 2, the liquid spreads on the hydrophilic gel layer, resulting in the aggregation of a large amount of liquid.

[0118] By establishing an in vitro physical model, stained water droplets (approximately 5 µL, containing 0.1% sodium fluorescein) were brought into contact with the oleogel-rich areas of sample A obtained in Example 1, sample B obtained in Comparative Example 1, and sample C obtained in Comparative Example 2, respectively. The transport process of the droplets under ultraviolet radiation (wavelength λ=254 nm) was monitored using a digital camera, and the results are shown in Figure 5.

[0119] from Figure 5It can be seen that when a droplet comes into contact with the surface of the oleogel-rich region of sample A obtained in Example 1 and sample C obtained in Comparative Example 2, the droplet can be rapidly pumped from the oleogel-rich region to the hydrogel-rich region through the microchannel, leaving an unwetted surface. However, when a droplet comes into contact with the surface of the oleogel-rich region of sample B obtained in Comparative Example 1, the droplet is rapidly wetted along its hydrogel layer and blocked by its oleogel layer, unable to reach the top. Compared with the interface-induced oil-hydrogel, sample B, which has not undergone interface induction, does not have this spontaneous liquid pumping ability. Furthermore, comparing sample A obtained in Example 1 with sample C obtained in Comparative Example 2, it can be found that sample A obtained in Example 1 has a faster liquid pumping rate.

[0120] Test 4: Antibacterial performance test.

[0121] A comparison chart of the antibacterial properties of sample A in Example 1 and sample B in Comparative Example 1 is shown below. Figure 6 As shown. The test method is as follows: using Staphylococcus aureus as a Gram-positive bacterium and Escherichia coli as a Gram-negative bacterium, the antibacterial activity of the hydrogel is tested, specifically including:

[0122] The bacteria were activated with liquid culture medium to obtain a bacterial suspension, which was then diluted with physiological saline to a concentration of 1×10⁻⁶. 5 CFU / mL was used to obtain a diluted bacterial suspension. Sample A from Example 1 and Sample B from Comparative Example 1 were added to the diluted bacterial suspension, serving as the experimental groups; the bacterial suspension without hydrogel was used as the control group. Both the experimental and control groups were incubated at 37°C and 120 rpm on a shaker for 24 h.

[0123] In the experimental group, the hydrogel concentration was 0.1 g / mL. After culturing for 24 h, the colony concentration of the control group was diluted to 1 × 10⁻⁶. 6 CFU / mL, and the experimental group was diluted by the same dilution factor. 100 μL of each solution was plated onto solid culture medium plates and incubated at 37°C for 24 hours. Colony counting was then performed. The bacterial count after incubation was as follows: Figure 6 As shown.

[0124] according to Figure 6 The results showed that both Sample A and Sample B hydrogels reduced the bacterial survival rate of Staphylococcus aureus and Escherichia coli to less than 1%, indicating that Sample A and Sample B have significant antibacterial effects.

[0125] Test 5: Analysis of the effects of oil-water gel dressings on the drainage of viscous fluids and the promotion of wound healing.

[0126] To further investigate the effects of sample A obtained in Example 1, sample B obtained in Comparative Example 1, and sample C obtained in Comparative Example 2 on the excretion of viscous fluid in the body and their potential role in promoting wound healing, a wound model was established in diabetic rats.

[0127] First, a diabetic rat model was established by intraperitoneal injection of streptozotocin (STZ) at a dose of 50 mg / kg. Eight days later, rats with fasting blood glucose levels higher than 16.7 mmol / L were selected as experimental rats. Subsequently, the rats were anesthetized with isoflurane, and four full-thickness wounds (8 mm in diameter) were created on the backs of the rats after hair removal and disinfection using an Integra Miltex circular biopsy puncture. The wounds were randomly divided into four groups: sample group A (Example 1), sample group B (Comparative Example 1), sample group C (Comparative Example 2), and a blank control group. The wounds were photographed and dressings changed on days 0, 2, 4, 6, 8, 10, and 12. The results are as follows: Figure 7 As shown.

[0128] from Figure 7 It can be seen that after a 12-day healing process, the open wound area of ​​sample A in Example 1 was significantly smaller than that of the other groups. More importantly, by day 8, the wound size of sample A in Example 1 had reached a similar level to that of the other groups by day 12, and the wound closure time was shortened by about 1 / 3.

[0129] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An oil-hydrogel dressing, characterized in that, The oil-water gel dressing includes an integral oil-water gel composite matrix, which is composed of a hydrogel enrichment region, an oil-water two-phase transition region and an oil gel enrichment region arranged sequentially along the thickness direction, and exhibits a continuously changing phase distribution. The oil-hydrogel composite matrix contains multiple conical microchannels that penetrate the hydrogel-rich region and the oil-rich region, and the pore walls of the conical microchannels are formed by hydrogel. The pore size of the conical microchannels gradually decreases from the oil-rich region to the hydrogel-rich region, which is used to drive the high-viscosity exudate to migrate directionally from the oil-rich region to the hydrogel-rich region.

2. The oil-hydrogel dressing according to claim 1, characterized in that, The two sides of the conical microchannel are a hydrophilic surface and a hydrophobic surface, respectively; the hydrophilic surface is located in the hydrogel-rich region and is formed by hydrogel; the hydrophobic surface is located in the oleogel-rich region and is formed by oleogel. The static water contact angle of the hydrophilic surface is less than 60°; the static water contact angle of the hydrophobic surface is greater than 110°.

3. The oil-hydrogel dressing according to claim 2, characterized in that, The continuously changing phase distribution is along the direction of directional migration of the high-viscosity exudate, with the mass fraction of oleogel gradually decreasing and the mass fraction of hydrogel gradually increasing. The pore size of the conical microchannel on the hydrophobic surface is 0.5 mm to 2 mm; the pore size of the conical microchannel on the hydrophilic surface is 0.1 mm to 1 mm, and the pore size of the conical microchannel on the hydrophilic surface is smaller than the pore size of the conical microchannel on the hydrophobic surface; and the center distance between adjacent conical microchannels is 3 mm to 7 mm.

4. The oil-hydrogel dressing according to claim 3, characterized in that, The conical microchannel has a pore size of 1.25 mm on the hydrophobic surface; the conical microchannel has a pore size of 0.75 mm on the hydrophilic surface; and the center-to-center distance between adjacent conical microchannels is 5 mm.

5. The oil-hydrogel dressing according to claim 1, characterized in that, The oil-water gel composite matrix is ​​formed by in-situ cross-linking polymerization and solidification of the oil gel and hydrogel at the oil-water interface due to the surface tension difference of the oil-water two-phase solution, and the resulting structure is composed of an integrated film layer structure consisting of a hydrogel enrichment region, an oil-water two-phase transition region and an oil gel enrichment region.

6. The oil-hydrogel dressing according to claim 5, characterized in that, The oil-hydrogel prepolymer solution is obtained by mixing an oil-hydrogel prepolymer solution and a hydrogel prepolymer solution. The hydrogel prepolymer solution is obtained by mixing the following raw materials in the indicated mass fractions: The composition consists of 10%–20% hydrogel monomer, 0.02%–0.05% first photoinitiator, 0.02%–0.05% first crosslinking agent, and the remainder is water, totaling 100%. The oleogel prepolymer solution is obtained by mixing the following raw materials in the indicated mass fractions: The second photoinitiator is 0.02% to 0.05%, the second crosslinking agent is 0.05% to 1%, and the remainder is oleogel monomer, totaling 100%.

7. The oil-hydrogel dressing according to claim 6, characterized in that, The hydrogel monomer is selected from at least one of hydroxyethyl methacrylate, acryloyloxyethyltrimethylammonium chloride, methacryloyloxyethylhexadecyldimethylammonium bromide, methacrylated alginate, methacrylated gelatin, methacrylated chitosan, and polyvinyl alcohol; The oleogel monomer is at least one of lauryl methacrylate, octadecyl acrylate, hexadecyl methacrylate, and benzyl methacrylate; The mass ratio of oleogel prepolymer to hydrogel prepolymer is 1:2 to 5; Both the first and second photoinitiators are 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone; the first crosslinking agent is nano-clay flakes and / or N,N-methylenebisacrylamide; and the second crosslinking agent is ethylene glycol dimethacrylate.

8. A molding die, characterized in that, For preparing the oil-hydrogel dressing according to any one of claims 1 to 7; the molding die includes: A hydrophilic template, wherein the surface of the hydrophilic template has a first hydrophilic modification layer; A micron-structured template having multiple conical cores configured on it, the conical cores having a geometry complementary to that of the conical microchannels; each conical core having a second hydrophilic modification layer on its surface; and the bottom of the micron-structured template having a hydrophobic surface layer. The hydrophilic template and the micron-structured template are combined to form a closed mold cavity.

9. The molding die according to claim 8, characterized in that, The water contact angle of the first hydrophilic modified layer is 0° to 60°; the water contact angle of the second hydrophilic modified layer is 0° to 60°; and the water contact angle of the hydrophobic surface layer is 120° to 170°.

10. A method for preparing an oil-hydrogel dressing, characterized in that, Includes the following steps: Prepare an oil-hydrogel prepolymer containing hydrogel monomers and olegel monomers; The oil-hydrogel prepolymer is injected into the molding mold of claim 8, so that the conical mold core is immersed in the oil-hydrogel prepolymer. After standing, the oil-hydrogel prepolymer is driven to undergo in-situ directional phase separation by utilizing the hydrophilic and hydrophobic differences of the inner surface of the molding mold. At an ambient temperature of 0℃~40℃, the molding mold containing the injected oil-hydrogel prepolymer is irradiated with ultraviolet light to induce in-situ cross-linking polymerization and solidification, locking the phase separation state; after demolding, an oil-hydrogel dressing with a heterogeneous phase distribution concentration gradient and a channel inner wall wettability gradient is obtained.